G.R.H. Wright, Ancient Building Technology, Volume 3, Construction, Technology and Change in History 12/1, Leiden: Brill 2009, ISBN 90 04 17745 1, Part I, 325pp + xxvi, Part 2, 415 pls, US$ 350. - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2012)
None